Three-Dimensional Magnetic Resonance Fingerprinting in Neonates: Quantifying Regional Difference and Maturation in the Brain. Issue 1 (January 2022) - Yu, Nali; Kim, Jee Young; Han, Dongyeob; Kim, So Young; Lee, Hye Mi; Kim, Dong-Hyun; Kim, Hyun Gi
Abstract : Objectives: Magnetic resonance fingerprinting (MRF) allows the simultaneous measurement of multiple tissue properties in a single acquisition. Three-dimensional (3D) MRF with high spatial resolution can be used for neonatal brain imaging. The aim of this study is to apply 3D MRF to neonates and show regional differences and maturation in the brain. Materials and Methods: In this prospective study, 3D MRF using hybrid radial-interleaved acquisition was performed on phantoms and neonates from December 2019 to October 2020. For the reconstruction of 3D MRF, singular value decomposition was applied to reduce reconstruction time, and the iterative reconstruction technique was applied to improve image quality. The accuracies of T1 and T2 values derived from 3D MRF were evaluated in a phantom experiment. Regional T1 and T2 values were obtained from neonates' brain T1 and T2 maps derived from 3D MRF. Regional T1 and T2 values were compared, and their changes according to corrected gestational age were evaluated. Results: The acquisition time for 3D MRF with a spatial resolution of 0.7 × 0.7 × 2 mm 3 was less than 5 minutes. The phantom study showed high correlation between T1 and T2 values derived from 3D MRF and those from conventional spin echo sequences (T1, R 2 = 0.998, P < 0.001; T2, R 2 = 0.998, P < 0.001). Three-dimensional MRF was performed in 25 neonates (15 boys, 10 girls; median corrected gestational age, 263 days; interquartile range, 10 days). In neonates, T1 and T2 values differed in the frontal (median [interquartile range], 2785 [2684–2888] milliseconds and 189.8 [176.7–222.9] milliseconds), parietal (2849 [2741–2950] milliseconds and 191.6 [167.5–232.9] milliseconds), and occipital white matter (2621 [2513–2722] milliseconds and 162.9 [143.5–186.1] milliseconds), showing lower values in occipital white matter ( P < 0.001). Regional T1 values showed a negative relationship with corrected gestational age (coefficient, −0.775 to −0.480; P < 0.05). Conclusions: Fast and high spatial resolution 3D MRF was applied to neonates. T1 and T2 maps derived from 3D MRF enabled the quantification of regional differences and maturation in the neonatal brain. Abstract : Supplemental digital content is available in the text.